Long-Term Athletic Development- Part 1: A Pathway for All Youth. Issue 5 (May 2015) - Lloyd, Rhodri S.; Oliver, Jon L.; Faigenbaum, Avery D.; Howard, Rick; De Ste Croix, Mark B. A.; Williams, Craig A.; Best, Thomas M.; Alvar, Brent A.; Micheli, Lyle J.; Thomas, D. Phillip; Hatfield, Disa L.; Cronin, John B.; et al.
Abstract : Abstract: Lloyd, RS, Oliver, JL, Faigenbaum, AD, Howard, R, De Ste Croix, MBA, Williams, CA, Best, TM, Alvar, BA, Micheli, LJ, Thomas, DP, Hatfield, DL, Cronin, JB, and Myer, GD. Long-term athletic development: Part 1: A pathway for all youth. J Strength Cond Res 29(5): 1439–1450, 2015—The concept of developing talent and athleticism in youth is the goal of many coaches and sports systems. Consequently, an increasing number of sporting organizations have adopted long-term athletic development models in an attempt to provide a structured approach to the training of youth. It is clear that maximizing sporting talent is an important goal of long-term athletic development models. However, ensuring that youth of all ages and abilities are provided with a strategic plan for the development of their health and physical fitness is also important to maximize physical activity participation rates, reduce the risk of sport- and activity-related injury, and to ensure long-term health and well-being. Critical reviews of independent models of long-term athletic development are already present within the literature; however, to the best of our knowledge, a comprehensive examination and review of the most prominent models does not exist. Additionally, considerations of modern day issues that may impact on the success of any long-term athletic development model are lacking, as are proposed solutions to address such issues. Therefore, within this 2-part commentary, Part 1 provides a critical review of existing models of practice for long-term athletic development and introduces a composite youth development model that includes the integration of talent, psychosocial and physical development across maturation. Part 2 identifies limiting factors that may restrict the success of such models and offers potential solutions.